Role of local eosinophilopoietic processes in the development of airway eosinophilia in prednisone‐dependent severe asthma. Issue 6 (June 2016) - Sehmi, R.; Smith, S. G.; Kjarsgaard, M.; Radford, K.; Boulet, L.‐P.; Lemiere, C.; Prazma, C. M.; Ortega, H.; Martin, J. G.; Nair, P.
Summary: Background: In severe asthmatics with persistent airway eosinophilia, blockade of interleukin‐5 has significant steroid‐sparing effects and attenuates blood and sputum eosinophilia. The contribution of local maturational processes of progenitors within the airways relative to the recruitment of mature cells from the peripheral circulation to the development of airway eosinophilia is not known. We hypothesize that local eosinophilopoiesis may be the predominant process that drives persistent airway eosinophilia and corticosteroid requirement in severe asthmatics. Objectives: In a cross‐sectional study, the number and growth potential of eosinophil‐lineage‐committed progenitors (EoP) were assayed in 21 severe eosinophilic asthmatics, 19 mild asthmatics, eight COPD patients and eight normal subjects. The effect of anti‐IL‐5 treatment on mature eosinophils and EoP numbers was made in severe eosinophilic asthmatics who participated in a randomized clinical trial of mepolizumab (substudy of a larger GSK sponsored global phase III trial, MEA115575) where subjects received mepolizumab (100 mg, n  = 9) or placebo ( n  = 8), as six monthly subcutaneous injections. Results: Mature eosinophil and EoP numbers were significantly greater in the sputum of severe asthmatics compared with all other subject groups. In colony‐forming assays, EoP from blood of severe asthmatics demonstrated a greater response to IL‐5 than mild asthmatics. Treatment of severe asthmatics with mepolizumab significantly attenuated blood eosinophils and increased EoP numbers consistent with blockade of systemic eosinophilopoiesis. There was however no significant treatment effect on mature eosinophils, sputum EoP numbers or the prednisone maintenance dose. Conclusions and Clinical Relevance: Patients with severe eosinophilic asthma have an exaggerated eosinophilopoeitic process in their airways. Treatment with 100 mg subcutaneous mepolizumab significantly attenuated systemic differentiation of eosinophils, but did not suppress local airway eosinophil differentiation to mature cells. Targeting IL‐5‐driven eosinophil differentiation locally within the lung maybe of relevance for optimal control of airway eosinophilia and asthma.